2015
DOI: 10.4236/oalib.1101289
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Associated Factors among Adult Individuals Receiving Highly Active Antiretroviral Therapy in Health Facilities of Hosanna Town, Southern Ethiopia

Abstract: Background: In resource limited settings, many human immunodeficiency virus (HIV) infected individuals lack access to sufficient quantities of nutritious foods, which poses additional challenges to the success of anti-retroviral therapy. Morbidity and mortality related to human immune deficiency virus infection in the developing world remain unacceptably high, despite major advances in human immune deficiency virus therapy and increased international funding for care. Objective: To determine magnitude of malnu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
6
8
3
Order By: Relevance
“…The proxy indicators of food insecurity used in this study to support the assessment of food insecurity also showed that significant number of people on ART (84.9%) and (69.4%) had low mean meal frequency and inadequate dietary diversified food, respectively. Similar findings were documented in Côte d'Ivoire and Uganda [14]- [16]. The results of this study indentified independent predictors of food insecurity; lower educational status, absence of food support, unemployment, poor and middle economic status were significantly associated with food insecurity at P < 0.05 among adult people on This has significant programmatic implication in that addressing the food insecurity issues among people on ART which is a critical element in achieving a better treatment and clinical outcome for ART.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The proxy indicators of food insecurity used in this study to support the assessment of food insecurity also showed that significant number of people on ART (84.9%) and (69.4%) had low mean meal frequency and inadequate dietary diversified food, respectively. Similar findings were documented in Côte d'Ivoire and Uganda [14]- [16]. The results of this study indentified independent predictors of food insecurity; lower educational status, absence of food support, unemployment, poor and middle economic status were significantly associated with food insecurity at P < 0.05 among adult people on This has significant programmatic implication in that addressing the food insecurity issues among people on ART which is a critical element in achieving a better treatment and clinical outcome for ART.…”
Section: Discussionsupporting
confidence: 71%
“…Results of the study showed that people on antiretroviral therapy suffer from food insecurity, majority 260 (67.5%) of the study participants were food insecure which is higher than the reports form study done in British Columbia, Canada [13] where 48% of people infected with HIV were food insecure, and also it is higher than the study done in Jimma, Ethiopia [9] where 63% of people infected with HIV were food insecure This high rate of food insecurity could be due to the variation in the socio economic status where as it is lower than the one reported from Ethiopia [12] [14]; this difference could be due to measurement difference of food insecurity like in Dire Dawa where measurement was taken at household level while the current study assessed the individual food insecurity experiences of participants. The proxy indicators of food insecurity used in this study to support the assessment of food insecurity also showed that significant number of people on ART (84.9%) and (69.4%) had low mean meal frequency and inadequate dietary diversified food, respectively.…”
Section: Discussioncontrasting
confidence: 53%
“…This implies that the signi cant number of peoples attending the ART clinicf developed under nutrition and HIV/AIDS has direct or indirect impact on nutritional status of the client those receiving HAART. The nding of this study was lower than the study done in Brazil [17] ,in Ethiopia: Bahir Dar [18], Dembia distric [12], Nekemte referral hospital [10], Wolaita Sodo [14], Butajira [11] and Hosana [9] which were 43%, 25.5%, 23.2%,27%, 26.6% 25.2% and 31.2% respectively. The discrepancy might be due to study period, increased health seeking behaviour of the community from time to time which enhance early detection and treatment of HIV, and other reason is due to difference in socioeconomic status of the community which has direct relation with under nutrition and increased government intervention like early initiation of HAART and supplementation diet.…”
Section: Resultscontrasting
confidence: 66%
“…In the present meta-analysis, four Ethiopian regions and one administrative town were represented. Five of the studies were from Amhara [4,[26][27][28][29], three from Oromia [24,30,31], five from Southern Region [25,[32][33][34][35], one from Tigray [36], and one from Addis Ababa [37]. However, no studies were located in Benishangul Gumiz, Harari, or Gagmbela regions.…”
Section: Characteristics Of Original Studiesmentioning
confidence: 99%
“…Regarding statistical quality and data presentation, the majority of studies had poor statistical quality and data presentation methods. Besides, to identify factors associated with malnutrition, the majority [4,[24][25][26][27][28][29][30][31][32][33][34][35][36] of studies used binary logistic regression model for analysis, but one of the studies used Pearson correlation coefficients to determine the associations association between nutritional and immunological status [37]. Concerning the model fitness test, only two studies reported about model fitness using Hosmer and Lemeshow goodness of fit test [29,33].…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%